Reducing the effects of scattered gamma photons in Tc-99m Myocardial SPECT imaging - Nazifah binti Abdullah (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2017)
Myocardial SPECT is one of the techniques that provide high diagnostic accuracy for the assessment of coronary artery disease. However, in general, the presence of Compton scattered photons in the resulting image data will reduce the diagnostic accuracy. This undesirable effect is even more significant in heart thorax-linked analysis compared to other regions with a more homogenous volume. In this study, the use of physical filter was proposed to reduce the undesirable scattered gamma photons. In this context, the scattered gamma photons were absorbed by the filter before they reach the gamma camera detector. Initially, a selection of the types and thickness of the filter materials based on a theoretical calculation was done. They were then incorporated into the basic procedures of Planar and SPECT imaging, and finally to Myocardial SPECT imaging, where a Tc-99m radionuclide was used. In Myocardial SPECT imaging procedure, an anthropomorphic torso (heart/thorax) phantom was used. The image reconstruction procedure was based on filtered back projection. Chang's attenuation correction method was used. The image quality was analyzed qualitatively and quantitatively. In Tc-99m spectra test, a decrease in the ratio of scattered to non-scattered photon for the whole spectra was observed for all types of the physical filters examined. However, the reduction in photopeak region was only recorded by Zn 0.2 mm filters. The physical filters were also found to improve system's spatial resolution, but the uniformity of the tomographic image was unchanged, and the system volume sensitivity was reduced to 16% for Cu and 4% for Zn filter. It was found that Zn 0.2 mm reduced the scatter in Myocardial SPECT imaging, where a clear separation between the liver and heart was observed. A significant improvement in contrast (10.98%) and signal-to-noise ratio of myocardial wall to defect areas (12.68%) was achieved with the use of Zn 0.2 mm material filter. Thus, it is concluded that the use of Zn 0.2 mm material filter has the potential to enhance the image quality in clinical SPECT imaging. However, clinical trials of this technique are required prior to its use in patient studies.